KCS1 and VIP1, the genes encoding yeast phosphoinositol pyrophosphate synthases, are required for Ca2+‐mediated response to dimethylsulfoxide (DMSO) - Larisa Ioana Gogianu; Lavinia Liliana Ruta; Claudia Valentina Popa; Simona Ghenea; Ileana Cornelia Farcasanu (FEBS Open Bio)
Dimethylsulfoxide (DMSO) is widely used as a solvent or as a carrier when screening for biologic activity of various chemicals, but results need to be interpreted carefully due to its intrinsic toxicity. DMSO has been previously observed to impair the growth of yeast cells defective in calcium movement across cellular membranes and in phosphoinositol pyrophosphate synthases. Here, we set out to investigate the Ca2+‐mediated response to DMSO in Saccharomyces cerevisiae. The cell exposure to DMSO was signaled by a two‐phase cytosolic Ca2+ wave that was dependent on Mid1, a subunit of the Cch1/Mid1 Ca2+ channel located at the plasma membrane. While the vacuolar Ca2+ channel Trpy1 also contributed by releasing Ca2+ from the vacuole, the immediate cell response to DMSO exposure depended on the external Ca2+ imported into the cell through Cch1/Mid1. A chemogenomic screen previously performed on a collection of yeast knockout mutants identified the two phosphoinositol pyrophosphate synthases Kcs1 and Vip1 as determinants for yeast tolerance to DMSO. Deletion of KCS1 or VIP1 genes suppressed the DMSO‐induced Ca2+ response, suggesting that both Ca2+ and phosphoinositol pyrophosphate signaling contribute to cell adaptation under DMSO stress.